Gambling as a Criminogenic Factor - Milošević, Slađana; Milošević, Višnja (Zbornik Instituta za kriminološka i sociološka istraživanja, 2020)
The aim of this paper is to consider the relationship between gambling as an already developed addiction on the one hand and criminal behavior on the other. The paper first presents the theoretical views and understandings of the nature of the relationship between gambling and crime, as well as several models that show the extent to which gambling contributes to a particular criminal behavior. Data from various studies confirm that the criminogenic effect of gambling can be distinguished in certain types of crime. The most common types of gambling-related crimes are financially motivated crimes such as theft, fraud, embezzlement, domestic violence, juvenile delinquency, and traffic delinquency. Consideration of the results also indicates a complex relationship between gambling and crime, and that this criminogenic factor should be paid more attention, especially in domestic criminological research.